Pengaruh Celebrity Endorsement, Promosi di Instagram, dan Online Customer Review Terhadap Minat Beli Konsumen Natur-E di Kota Batam - Yohana, Selvi; Luthfi, Andi Mulyadi; Raymond, Raymond (Universitas Batam, 2024)
The increasing interest in the internet and buying and selling activities through digital platforms in the beauty and health category has changed the way Indonesian consumers shop, resulting in competition among entrepreneurs. Natur-e by continuing to try to increase consumer buying interest in their products through celebrity endorsements, promotions on instagram, and online customer review, but Natur-e has not managed this well as evidenced by the sales volume of Natur-e fluctuating every year. The purpose of this study was to determine the effect of celebrity endorsement, promotion on instagram, and online customer reviews on consumer buying interest in Natur-e in Batam City. The findings in this study partially are celebrity endorsement has a positive and significant effect, promotion on instagram has a positive and insignificant effect, and online customer review have a positive and significant effect on consumer buying interest in Natur-e in Batam City. Simultaneously celebrity endorsement, promotion on instagram, and online customer review have a positive and significant influence on consumer buying interest.